Remembrance, Remembering, Forgetting Childhood in Topsy Turvy Talk by Aleksander Fredro - Dąbrowska, Alicja (Porównania, 2023)
Childhood and youth are an important theme/topic in Fredro’s diary from the Napoleonic era. In this article, I intend to reconstruct the specificity and analyse the memory of images of childhood in its most crucial liminal phases in Trzy po trzy (Topsy Turvy Talk). The aim is to discuss this text, which constitutes the sum of genres (storytelling, diary, etc.), deciphering how the author starts remembering and forgetting. How he activates the category of “vertical memory” (Proust), which guarantees the veracity of recollection, emanating from within the recollector, for whom the “immaterial” senses of smell, sight, hearing allow memory, through sensory association, to “recollect” the essentials of childhood.